2021
DOI: 10.3802/jgo.2021.32.e4
|View full text |Cite
|
Sign up to set email alerts
|

The extent of aortic lymphadenectomy in locally advanced cervical cancer impacts on survival

Abstract: Objective: The prognostic impact of surgical paraaortic staging remains unclear in patients with locally advanced cervical cancer (LACC). The objective of our study was to evaluate the results of the surgical technique of preoperative aortic lymphadenectomy in LACC related to tumor burden and disease spread to assess its influence on survival. Methods: Data of 1,072 patients with cervical cancer were taken from 11 Spanish hospitals (Spain-Gynecologic Oncology Group [GOG] working group). Complete aortic lymphad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 30 publications
(17 reference statements)
0
3
0
Order By: Relevance
“…Authors found positive PALNs in 119 women. Skip metastasis in the supramesenteric region was found in 18% of lymph nodes retrieved, without the presence of a metastases inframesenteric region [17]. According to these studies, we concluded that the LRV should be considered as the ventral limit of PALND for patients with cervical cancer and suspected PALNs' metastases.…”
Section: Boundaries Of Palnd In Gynecological Malignanciesmentioning
confidence: 80%
See 2 more Smart Citations
“…Authors found positive PALNs in 119 women. Skip metastasis in the supramesenteric region was found in 18% of lymph nodes retrieved, without the presence of a metastases inframesenteric region [17]. According to these studies, we concluded that the LRV should be considered as the ventral limit of PALND for patients with cervical cancer and suspected PALNs' metastases.…”
Section: Boundaries Of Palnd In Gynecological Malignanciesmentioning
confidence: 80%
“…Authors found positive PALNs in 119 women. Skip metastasis in the supramesenteric region was found in 18% of lymph nodes retrieved, without the presence of a metastases inframesenteric region [17].…”
Section: Boundaries Of Palnd In Gynecological Malignanciesmentioning
confidence: 92%
See 1 more Smart Citation